Development of honda supra manual transmission system demo made in acrylic to improve students' learning outcomes at muhammadiyah 04 vocational school sukorejo - Yogi Kurniawan; Naryanto , Rizqi Fitri; Septiyanto, Angga (JMEL : Journal of Mechanical Engineering Learning, 2025)
Based on the results of observations at SMK Muhammadiyah 04 Sukorejo, it is known that there is still no Honda manual transmission demonstration tool which makes it difficult to understand and comprehend the material presented by the teacher, especially in the basic competency of repairing and periodically maintaining the motorcycle manual transmission system. This study aims to develop a motorcycle manual transmission demonstration learning media that is feasible and can improve student learning outcomes. This study uses the Research and Development (R&D) research method with the ADDIE model. The subjects of this study were grade 11 students of TBSM 1 SMK Muhammadiyah 04 Sukorejo. Product trials were carried out at the implementation stage using the trial stage with the One-Group Pretest-Posttest Design model. The results of the media expert assessment obtained a percentage of 82.5% and the material expert with a percentage of 86.45%. The results of the pretest stage test obtained a value with an average of 64.11 and the posttest stage obtained a value with an average of 79.00. The motorcycle manual transmission system demonstration tool is included in the "very satisfying" category based on student perceptions with a percentage of 82.5%. Based on the results of the N-gain test, the motorcycle manual transmission teaching aid was proven to be able to improve students' mastery of competencies in the moderate category (gain value of 0.414 is between 0.7 > N-gain ≥ 0.03), and based on the t-test, the results showed that the average mastery of student competencies was more than KKM 75 (Sig. Value 0.40 > 0.05).